Applications of dynamic combinatorial chemistry for the determination of effective molarity. Issue 1 (29th September 2014) - Ciaccia, Maria; Tosi, Irene; Baldini, Laura; Cacciapaglia, Roberta; Mandolini, Luigi; Di Stefano, Stefano; Hunter, Christopher A.
Abstract : Chain-stoppers give rise to ring-chain equilibria in dynamic libraries allowing determination of thermodynamic effective molarities for macrocylisation reactions. Abstract : A new strategy for determining thermodynamic effective molarities (EM) for macrocylisation reactions using dynamic combinatorial chemistry under dilute conditions is presented. At low concentrations, below the critical value, Dynamic Libraries (DLs) of bifunctional building blocks contain only cyclic species, so it is not possible to quantify the equilibria between linear and cyclic species. However, addition of a monofunctional chain stopper can be used to promote the formation of linear oligomers allowing measurement of EM for all cyclic species present in the DL. The effectiveness of this approach was demonstrated for DLs generated from mixtures of 1, 3-diimine calix[4]arenes, linear diaminoalkanes and monoaminoalkanes. For macrocycles deriving from one bifunctional calixarene and one diamine, there is an alternating pattern of EM values with the number of methylene units in the diamine: odd numbers give significantly higher EMs than even numbers. For odd numbers of methylene units, the alkyl chain can adopt an extended all anti conformation, whereas for even numbers of methylene units, gauche conformations are required for cyclisation, and the associated strain reduces EM. The value of EM for the five-carbon linker indicates that this macrocycle is a strainless ring.